Hidden order [compact disc, unabridged] - Thor, Brad (Thor, Brad. Scot Harvath., 2013)
A string of high-profile kidnappings has Washington, D.C. in frenzy. When the victims begin turning up dead, frenzy turns to panic. And when the ransom demand is finally made public, panic will turn to terror. The stakes have never been higher, nor the lines between good and evil so hard to discern.